PENGARUH PERILAKU PEMIMPIN TERHADAP KINERJA KARYAWAN PT. BANK TABUNGAN NEGARA (PERSERO) TBK. KANTOR CABANG MANADO - Anzhari, Irvan; Sumampouw, Harry; Kaparang, Sonny (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. This study aims to investigate the influence of leader behaviors on employee performance. In this research uses descriptive quantitative approach to measure the relationship between the variables of leadership behavior and employee performance. The population in this study as many as 66 people, while the total sample of 45 respondents by means of simple regression analysis. The results showed that the behavior of the leader of a significant effect on the performance of employees of PT Bank BTN (Persero), Tbk. Branch Office Manado. Therefore, should a leader must be able to demonstrate its capacity in order to improve employee performance.Keywords: Behavior Leader, Employee Performance